2020
DOI: 10.3390/en13236321
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Multiple-Criteria Decision-Making Method for Evaluation of Sustainable Energy Development: A Case Study of Poland

Abstract: One of the basic objectives of the European Union’s energy policy is to obtain and use energy in a sustainable way. Multiple-criteria decision making (MCDM) methods, in particular linear ordering based on the synthetic variable procedure, are used for comparative analyses of the level of energy sustainability. Despite many studies, the problem of choosing the optimal ordering method is still not fully resolved. This paper presents an original procedure that facilitates the selection of an effective method of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…With the DEA method, it is possible to determine not only fully effective objects but also those that are not fully effective. This method is widely used in research in the field of energy management [27,34]. This method, however, goes beyond the purpose of the research adopted in the paper but is an indicator of future research by the authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the DEA method, it is possible to determine not only fully effective objects but also those that are not fully effective. This method is widely used in research in the field of energy management [27,34]. This method, however, goes beyond the purpose of the research adopted in the paper but is an indicator of future research by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors do not study the impact of changes in the structure of these energy sources on the development potential of the energy sector itself, which is the subject of this article. Moreover, it can be noted that thematically compatible, available research on the energy production sector is mainly based on statistical methods of data analysis, as for example simple additive weighting (SAW) [27], technique for order of preference by similarity to ideal solution (TOPSIS) [28], data envelopment analysis (DEA) [29,30], the fully-modified least square (FMOLS) method [23] etc. Nevertheless, most of the studies in this field refer to a specific economy of a given country, and do not cover such a large group of countries as in the European Union.…”
Section: The Change Of Perception Of Energy Sources-literature Reviewmentioning
confidence: 99%
“…The model was applied to a case study in Vietnam and the result showed that the optimal location for a hydroelectric plant is Nghe An Province. Trojanowska and Nęcka [24] performed a comparative research of four different MCDM methods-simple additive weighting (SAW), synthetic measure of development (SMD), weighted aggregated sum product assessment (WASPAS), and TOPSIS-in solving the sustainable energy development evaluation problem. As a result, the SMD method was the preferred method for the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ten variables belong to stimulants, i.e., the indicators x 1 -x 10 , and five indicators belong to destimulants, i.e., x 11 -x 15 . The indicators where the maximalization is positive are stimulants and the variables where the minimalization is positively rated are destimulants [69][70][71].…”
Section: Status and Development Of Indicatorsmentioning
confidence: 99%